A review of heat stress in chickens. Part II: Insights into protein and energy utilization and feeding - Teyssier, Jean-Rémi; Brugaletta, Giorgio; Sirri, Federico; Dridi, Sami; Rochell, Samuel J. (Frontiers in Physiology, 2022)
With the growing global demand for animal protein and rising temperatures caused by climate change, heat stress (HS) is one of the main emerging environmental challenges for the poultry industry. Commercially-reared birds are particularly sensitive to hot temperatures, so adopting production systems that mitigate the adverse effects of HS on bird performance is essential and requires a holistic approach. Feeding and nutrition can play important roles in limiting the heat load on birds; therefore, this review aims to describe the effects of HS on feed intake (FI) and nutrient digestibility and to highlight feeding strategies and nutritional solutions to potentially mitigate some of the deleterious effects of HS on broiler chickens. The reduction of FI is one of the main behavioral changes induced by hot temperatures as birds attempt to limit heat production associated with the digestion, absorption, and metabolism of nutrients. Although the intensity and length of the heat period influences the type and magnitude of responses, reduced FI explains most of the performance degradation observed in HS broilers, while reduced nutrient digestibility appears to only explain a small proportion of impaired feed efficiency following HS. Targeted feeding strategies, including feed restriction and withdrawal, dual feeding, and wet feeding, have showed some promising results under hot temperatures, but these can be difficult to implement in intensive rearing systems. Concerning diet composition, feeding increased nutrient and energy diets can potentially compensate for decreased FI during HS. Indeed, high energy and high crude protein diets have both been shown to improve bird performance under HS conditions. Specifically, positive results may be obtained with increased added fat concentrations since lipids have a lower thermogenic effect compared to proteins and carbohydrates. Moreover, increased supplementation of some essential amino acids can help support increased amino acid requirements for maintenance functions caused by HS. Further research to better characterize and advance these nutritional strategies will help establish economically viable solutions to enhance productivity, heath, welfare, and meat quality of broilers facing HS.